Protective potential of Bacopa monniera (Brahmi) extract on aluminum induced cerebellar toxicity and associated neuromuscular status in aged rats - Tripathi, S.; Mahdi, A. A.; Hasan, M.; Mitra, K.; Mahdi, F. (Cellular and Molecular Biology, 2011)
The present study attempts to assess the comparative effects of Bacopa monniera, (40 mg/kg body weight) and donepezil (2.5 mg/kg b. wt) on aluminum (100 mg / kg b. wt. of AlCl3) mediated oxidative damage in the cerebellum of aged rats (24 months) along with the associated dysfunctioning of neuromuscular coordination and motor activity. A significant decrease in the activities of antioxidant enzymes and increased total reacting oxygen species, lipid and protein peroxidation products observed in aluminum exposed rats. We observed that treatment with B. monniera extract restored the altered antioxidant enzyme activities more, when compared with donepezil. However, acetylcholinesterase showed similar effect both in donepezil and B. monniera treated groups. The content of aluminum was increased in all experimental groups, however, iron content was found increased in all groups except the B. monniera treated groups. Moreover, aluminum treated groups of rats exhibited significant changes in behavioral profiles but these changes were in both B. monniera and donepezil treated groups. The light microscopic and ultrastructural studies revealed damaged Purkinje's neurons and altered granular cell layer along with the increased accumulation of lipofuscin granules in aluminum treated animals. These changes were quite less pronounced in B. monniera group than that of donepezil and this may be due to the reduction of excess iron content by B. monniera. On the basis of our results it may be concluded that Al may be linked with cerebellar degeneration and neuromuscular disorders while Bacopa monniera extract helps in reversing these changes.